Cruise Ship Travel in the Era of Coronavirus Disease 2019 (COVID-19): A Summary of Outbreaks and a Model of Public Health Interventions. (12th May 2021) - Guagliardo, Sarah Anne J; Prasad, Pragati V; Rodriguez, Andrea; Fukunaga, Rena; Novak, Ryan T; Ahart, Lauren; Reynolds, Jared; Griffin, Isabel; Wiegand, Ryan; Quilter, Laura A S; Morrison, Stephanie; Jenkins, Keisha; et al.
Abstract: Background: Cruise travel contributed to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission when there were relatively few cases in the United States. By 14 March 2020, the Centers for Disease Control and Prevention (CDC) issued a No Sail Order suspending US cruise operations; the last US passenger ship docked on 16 April. Methods: We analyzed SARS-CoV-2 outbreaks on cruises in US waters or carrying US citizens and used regression models to compare voyage characteristics. We used compartmental models to simulate the potential impact of 4 interventions (screening for coronavirus disease 2019 (COVID-19) symptoms; viral testing on 2 days and isolation of positive persons; reduction of passengers by 40%, crew by 20%, and reducing port visits to 1) for 7-day and 14-day voyages. Results: During 19 January to 16 April 2020, 89 voyages on 70 ships had known SARS-CoV-2 outbreaks; 16 ships had recurrent outbreaks. There were 1669 reverse transcription polymerase chain reaction (RT-PCR)-confirmed SARS-CoV-2 infections and 29 confirmed deaths. Longer voyages were associated with more cases (adjusted incidence rate ratio, 1.10, 95% confidence interval [CI]: 1.03–1.17, P < .003). Mathematical models showed that 7-day voyages had about 70% fewer cases than 14-day voyages. On 7-day voyages, the most effective interventions were reducing the number of individuals onboard (43.3% reduction in total infections) and testing passengers and crew (42% reduction in total infections). All four interventions reduced transmission by 80.1%, but no single intervention or combination eliminated transmission. Results were similar for 14-day voyages. Conclusions: SARS-CoV-2 outbreaks on cruises were common during January–April 2020. Despite all interventions modeled, cruise travel still poses a significant SARS-CoV-2 transmission risk. Abstract : We analyze the largest available dataset on SARS-CoV-2 on cruises, and assess interventions using mathematical modeling. Even with stringent control measures in place, the risk of SARS-CoV-2 on board cruise ships cannot be eliminated while there is sustained community transmission.